Comparing Anti-apoptotic Effects of Peroxisome Proliferator-Activated Receptor-Gamma and Angiotensin-Converting Enzyme Inhibitors using Human Umbilical Vein Endothelial Cells Exposed to Sera from Patients with Alzheimer’s Disease and Healthy Controls - Rokhsareh Meamar; Majid Ghasemi; Leila Dehghani (مجله دانشکده پزشکی اصفهان, 2014)
Background: Alzheimer's disease (AD), the most frequent progressive neurodegenerative disorder, is associated with endothelial cell dysfunction. It has been presented that peroxisome proliferator-activated receptor-gamma (PPAR-gamma) agonists can attenuate neurodegeneration of experimental autoimmune encephalomyelitis (EAE) and improve vascular function. On the other hand, angiotensin-converting enzyme inhibitors (ACE-I) has beneficial effects on endothelial dysfunction and endothelial surveillance. This study aimed to compare the beneficial effects of PPAR-gamma and ACE-I on human umbilical vein endothelial cells (HUVECs) treated with sera from patients with Alzheimer's disease or healthy controls.